TRANSFORMATION TO PROTOTROPHY AND POLYGLUTAMIC ACID SYNTHESIS IN BACILLUS LICHENIFORMIS - Leonard, C. Gomez (1964)
Leonard, C. Gomez (U.S. Army Biological Laboratories, Fort Detrick, Frederick, Md.), D. K. Mattheis, M. J. Mattheis, and R. D. Housewright. Transformation to prototrophy and polyglutamic acid synthesis in Bacillus licheniformis. J. Bacteriol. 88:220–225. 1964.—Growth conditions necessary for transformation to prototrophy of 14 auxotrophs of Bacillus licheniformis were studied. The unexpected finding of different growth requirements by each auxotroph for the development of transformable cells is discussed. Under optimal growth conditions for a serine-deficient mutant transformation frequencies of 0.1% were obtained. A medium for transformation of competent cells in liquid suspensions is described. In addition, this report presents evidence for the transformation of three nonencapsulated mutants of B. licheniformis for the ability to synthesize polyglutamic acid (capsular material).